3m+2=4m-6

Simple and best practice solution for 3m+2=4m-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+2=4m-6 equation:


Simplifying
3m + 2 = 4m + -6

Reorder the terms:
2 + 3m = 4m + -6

Reorder the terms:
2 + 3m = -6 + 4m

Solving
2 + 3m = -6 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
2 + 3m + -4m = -6 + 4m + -4m

Combine like terms: 3m + -4m = -1m
2 + -1m = -6 + 4m + -4m

Combine like terms: 4m + -4m = 0
2 + -1m = -6 + 0
2 + -1m = -6

Add '-2' to each side of the equation.
2 + -2 + -1m = -6 + -2

Combine like terms: 2 + -2 = 0
0 + -1m = -6 + -2
-1m = -6 + -2

Combine like terms: -6 + -2 = -8
-1m = -8

Divide each side by '-1'.
m = 8

Simplifying
m = 8

See similar equations:

| 9+1/2x=5x-1 | | 17a-8(a+1)=3(a-3) | | 1/x=98.78 | | -x+14=7+x | | 3(x+4)=5-(x-11) | | 6x+5=8+6x | | 6-q=4-2q | | 5r-2=-r+4 | | -2.3c=11.5 | | 2x+7=11-7x | | -12x=3 | | 7x+11=11x+12 | | 50x^2+200=0 | | 3x-12/6+x/30=x/5-1 | | 12x+18=2(6x+3) | | 9x=8(3x+5) | | 5/7(x+1)=1/21(x+6) | | -4=(-4m+9+m)3-13 | | 4x+9=47/5+3x | | 14x^3+(3x+8x^3)= | | 9x^2+270=0 | | 94-5x=13x+16 | | 16x-(3x-7)=12 | | -5/6x+1=5/18 | | 3y+12=3(4+y) | | -(-5+5p)+6p=-8 | | 8=15-c/3 | | y=7-(1) | | y=7-(0) | | 3p-1=5(9-1) | | 21-7b=-4+5(8b+5) | | y=7-(-1) |

Equations solver categories